2003
DOI: 10.1590/s1516-84842003000300011
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da refratariedade plaquetária em pacientes submetidos ao transplante de medula óssea do dia 0 ao dia + 50

Abstract: Resumo de Tese / Thesis Estudo da refratariedade plaquetária em pacientes submetidos ao transplante de medula óssea do dia 0 ao dia + 50

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The frequency of this complication in oncohematological patients varies depending on the study; in a recent analysis of the TRAP (Trial to Reduce Alloimmunization to Platelets) Study, platelet refractoriness developed in 27% of patients with acute leukemia ( 5 ) . In Brazil, a single center study published in 2004 describes an extremely high frequency, with 80% of patients developing this complication in the early phase of hematopoietic stem cell transplantation ( 6 ) . However, in a more recent study, a 19% frequency of platelet refractoriness, much closer to data of several other studies, was demonstrated among oncohematological patients ( 7 ) .…”
mentioning
confidence: 99%
“…The frequency of this complication in oncohematological patients varies depending on the study; in a recent analysis of the TRAP (Trial to Reduce Alloimmunization to Platelets) Study, platelet refractoriness developed in 27% of patients with acute leukemia ( 5 ) . In Brazil, a single center study published in 2004 describes an extremely high frequency, with 80% of patients developing this complication in the early phase of hematopoietic stem cell transplantation ( 6 ) . However, in a more recent study, a 19% frequency of platelet refractoriness, much closer to data of several other studies, was demonstrated among oncohematological patients ( 7 ) .…”
mentioning
confidence: 99%